The Influence of Institutional Ownership, Sharia Supervisory Board, Board of Directors, and Company Size on Profitability with Islamic Social Reporting as a Moderating Variable - Ilham Nurhabibie; Iwan Fakhruddin; Hadi Pramono; Dwi Winarni (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to examine the effect of institutional ownership, sharia supervisory board, board of directors, and company size on profitability with Islamic social reporting as a moderating variable. The sample used in this research is Islamic Commercial Banks in 2015-2021 with a total of 96 samples. The data analysis technique used is panel data regression analysis. Analysis of the 3 stages of the test, namely the preliminary test which will determine the model used through the chow test, Breush and pagan lagrangian multiplier test, and Hausman test. Based on the results of the three preliminary tests, this research will use a fixed effect model to examine the relationship between variables. Then the diagnostic tests, namely heteroscedasticity and autocorrelation, are continued with hypothesis testing.